Site-specific reproductive performance of an invasive fleshy-fruited tree in remnant grasslands of the Argentinean Pampas - Zalba, Sergio Martin (2015)
Prunus mahaleb (Saint Lucie´s cherry) is a fleshy-fruited small rosaceous tree, native to the Mediterranean region that has been extensively used as a rootstock species for commercial orchard trees. It has been widely introduced in several countries, becoming invasive in many regions, including the Pampas region of southern Argentina. We studied the reproductive performance of trees spontaneously growing in natural grasslands inside a protected area, estimating age at first reproduction and analysing changes in fruit production, age, canopy volume and basal stem diameter associated with different soil types: rock crevices on hillsides, deep soils in valleys and deep soils in stream-side habitats. Fruit production starts at the age of 3?6 years, and it can be abundant, even for young plants. We found evidence that fecundity is related to plant size, and that the age at which individuals reach a particular size and begin fruiting differs depending on the soil type where they grow. Trees in the study area show an order of magnitude increase in fruit production on reaching ages from 7 to 10 years for plants growing in deep soils at stream-side habitats and 13?16 years for plants growing in rock crevices. Invasive trees should be felled before they reach a basal stem diameter of c. 9 cm to avoid this increase in propagule pressure. Considering that the age at which this stage is reached depends on soil type, the streams could act as dispersal corridors for the spread and invasion of this species.